Distinctive electroluminescence characteristics behind efficient mesoscopic perovskite solar cell. (15th June 2018) - Wang, Minhuan; Bian, Jiming; Feng, Yulin; Dong, Qingshun; Zhang, Bingye; Liu, Hongzhu; Shi, Yantao
Abstract: Metal halide perovskites are emerging as exceptional class of materials due to its unprecedented collective advantages for optoelectronic applications. Here, the efficient mesoscopic perovskite solar cells (M-PSCs) with the architecture of FTO-SnO2 /m-TiO2 + MAPbI3 /Spiro-OMeTAD/Ag were synthesized, where the discontinuous SnO2 derived blended-interfacial-layer worked as electron transport layer (ETL). A moderate power conversion efficiencies (PCEs) of 17.42% was achieved. Notably, a 10 s level ultra-long rise time in time-resolved electroluminescence (EL) characteristics was observed from the same device as the MAPbI3 perovskite layer served as light emitter. Such performance was attributed to the reasonable device design based on the dynamics favorable electron transport layer. This achievement would be beneficial for further understanding the working mechanism of perovskite-based optical-to-electrical and electrical-to-optical conversion devices.